2022
DOI: 10.1002/erv.2893
|View full text |Cite
|
Sign up to set email alerts
|

Early within‐person weight gain and variability during inpatient treatment for anorexia nervosa: Age‐dependent effects on treatment outcome

Abstract: Objective Early weight gain during inpatient treatment for anorexia nervosa (AN) is a dynamic process characterised by within‐person variability that may be age‐dependent. We examined whether age moderates the effect of within‐person weight gain and variability on treatment outcome. Method Within‐person level estimates of N = 2881 underweight adolescents and adults with AN for daily average weight gain (linear slope) and variability (root mean squared errors) were obtained using random‐effects modelling. Betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is important to note that the effects of weight fluctuations, as measured by the degree of variation around a patient’s weight regression line, have thus far only been investigated for AN in two studies, with varying results. Whereas Kolar et al [ 10 ] found no effects of weight variability on treatment outcomes in adolescent and adult patients, higher weight variability predicted poorer weight gain in adults in Hartmann et al [ 11 ]. Besides the difference in sample choice, neither study analyzed effects of weight variability stratified by gender; this might be a further explanation for the reported discrepancies between studies and highlights the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that the effects of weight fluctuations, as measured by the degree of variation around a patient’s weight regression line, have thus far only been investigated for AN in two studies, with varying results. Whereas Kolar et al [ 10 ] found no effects of weight variability on treatment outcomes in adolescent and adult patients, higher weight variability predicted poorer weight gain in adults in Hartmann et al [ 11 ]. Besides the difference in sample choice, neither study analyzed effects of weight variability stratified by gender; this might be a further explanation for the reported discrepancies between studies and highlights the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…BMI-SDS shows the deviation of a patient’s BMI from the population mean and allows for age- and gender-adjusted body weight comparisons. Similar to previous studies [ 10 , 36 ], we then computed daily weight change and weight variability within the first two weeks of treatment (starting with day 0 at admission and ending on day 13), using the slopes and root-mean-squared errors (RMSE) of residuals from a linear mixed model. The model used changes (increase or decrease) from baseline BMI-SDS to current BMI-SDS as dependent variable, and included an intercept and a fixed effect of day of treatments, with by-patient random variation of slope and intercept.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations